WEB-BASED CLOTHING SALES INFORMATION SYSTEM FOR FREYEAYCLOTHING MICRO AND MEDIUM ENTERPRISES - Terris Aldio Rahmad Santoso; Suhendro Busono (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to design and implement a web-based sales information system for the micro and medium enterprise “FreyeayClothing” to overcome challenges in managing sales transactions, inventory, and financial reporting efficiently. Method: The system was developed using the Agile development methodology, which involves iterative stages of planning, designing, developing, testing, and deployment to ensure adaptability and continuous improvement based on user feedback. Results: The implementation of this web-based system significantly enhanced operational efficiency, particularly in the management of sales and inventory data. The automated processes reduced manual errors, improved data accuracy, and provided timely access to sales information. Additionally, the system’s reporting features supported more effective business decision-making through real-time financial insights. Novelty: The novelty of this research lies in the application of the Agile method for developing a scalable and adaptive web-based information system specifically tailored for micro and medium enterprises, demonstrating its effectiveness in improving digital transformation and decision-making processes in small-scale retail operations.